Hubungan Pemberian Asi Eksklusif dengan Kejadian Stunting Pada Balita Umur 24-59 Bulan - Mega Purnamasari; Teti Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Stunting is a condition of toddlers who have less length or height when compared to age. Stunting can be caused by giving. The aim of describing the relationship between exclusive breastfeeding and the incidence of stunting in infants aged 24-59 months. Method; study literature results; studies show that exclusive breastfeeding has a significant relationship with the incidence of stunting in toddlers aged 24-59 months. Conclusion; where toddlers who are exclusively breastfed will reduce the risk of stunting